2010
DOI: 10.1007/s11199-010-9869-0
|View full text |Cite
|
Sign up to set email alerts
|

Benevolent Sexism, Perceived Health Risks, and the Inclination to Restrict Pregnant Women’s Freedoms

Abstract: The present study investigated the role of sexist ideology in perceptions of health risks during pregnancy and willingness to intervene on pregnant women's behavior. Initially, 160 female psychology undergraduates at a university in the South East of England completed the Ambivalent Sexism Inventory (Glick & Fiske, 1996). Two months later, in an apparently unrelated study, they rated the safety of 45 behaviours during pregnancy (e.g., drinking alcohol, exercising, drinking tap water, and oral sex), and indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 29 publications
2
45
0
1
Order By: Relevance
“…For example, benevolent and hostile sexism were related to attitudes toward dating and sexual behavior (McCarty and Kelly 2015;Paynter and Leaper 2016;Zaikman and Marks 2014), tolerance of sexual harassment and rape (Durán et al 2016;Russell and Trigg 2004), and attitudes toward women's reproductive rights, pregnancy, and abortion (Hodson and MacInnis 2017;Huang et al 2016;Sutton et al 2011). Particularly important for our purposes, many findings indicate that sexist attitudes affect relationship and marriage norms and promote preferences for romantic partners who possess qualities congruent with traditional gender roles (Bermúdez et al 2015;Chen et al 2009;Thomae and Houston 2016).…”
Section: Ambivalent Sexism Theorymentioning
confidence: 86%
“…For example, benevolent and hostile sexism were related to attitudes toward dating and sexual behavior (McCarty and Kelly 2015;Paynter and Leaper 2016;Zaikman and Marks 2014), tolerance of sexual harassment and rape (Durán et al 2016;Russell and Trigg 2004), and attitudes toward women's reproductive rights, pregnancy, and abortion (Hodson and MacInnis 2017;Huang et al 2016;Sutton et al 2011). Particularly important for our purposes, many findings indicate that sexist attitudes affect relationship and marriage norms and promote preferences for romantic partners who possess qualities congruent with traditional gender roles (Bermúdez et al 2015;Chen et al 2009;Thomae and Houston 2016).…”
Section: Ambivalent Sexism Theorymentioning
confidence: 86%
“…Information from professionals should be accurate and appropriately communicated, but women weigh this information alongside information from other sources and in the wider context of everyday life (Alaszewski and Horlick-Jones 2003). The study by Sutton (2010) which found willingness to intervene when a pregnant woman was observed doing something perceived to present a risk did not have an association with perceived level of knowledge of pregnancy, suggests risk in pregnancy remains an emotive subject of which factual knowledge is only one aspect. Healthcare professionals should therefore remember that women will take many factors into account when assessing their perceived degree of risk and not assume that statistical information about risk or an increased amount of factual information will be the most influential of these.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that pregnant women are widely regarded as an especially vulnerable group in need of increased monitoring and intervention (Lupton 1999). This desire to control the behaviour of pregnant women in order to protect them from perceived danger has been shown to extend beyond the medical profession (Sutton, Douglas et al 2010). In a study of US female undergraduates, Sutton et al used questionnaires to assess levels of sexism, knowledge of pregnancy, and perceived willingness to intervene if a pregnant woman was witnessed doing something perceived as unsafe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barlow et al (2008) reported that asymptomatic pregnant women diagnosed with hypertension felt uncomfortable receiving medical care and had difficulty following treatment plans. Finally, beliefs about what constitutes a risk may be incorrect but based on ingrained cultural myths and stereotypes about health and pregnancy (Sutton et al 2011).…”
Section: Comparison With Professionals' Risk Perceptionmentioning
confidence: 99%